2018
DOI: 10.1177/1350508417703472
|View full text |Cite
|
Sign up to set email alerts
|

On interference, collegiality and co-authorship: Peer review of journal articles in management and organization studies

Abstract: Management and organization studies commentary on how authors experience peer review of journal papers suggests it can be an overly interventionist process which reduces the originality and coherence of eventual publications. In the literature on coauthorship, this argument is reversed. Here free riders who do not contribute fully to research collaborations and the practice of gift authorships are problematized; and it is argued that everyone involved in writing a published paper should be rewarded with co-aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 67 publications
0
14
0
Order By: Relevance
“…The storied academic text: research participated in, written, edited, reviewed; multi-voiced in layering, foregrounding, backgrounding. Bodied co-authors shadowed in the writing process, writing back to us in creation – liberation or constraint (Brewis, 2018b). Wikipedia, that shifting, thin-skinned itch-to-scratch, states that ‘Parchment is affected by its environment and changes in humidity, which can cause buckling’.…”
Section: Writing As Palimpsestmentioning
confidence: 99%
“…The storied academic text: research participated in, written, edited, reviewed; multi-voiced in layering, foregrounding, backgrounding. Bodied co-authors shadowed in the writing process, writing back to us in creation – liberation or constraint (Brewis, 2018b). Wikipedia, that shifting, thin-skinned itch-to-scratch, states that ‘Parchment is affected by its environment and changes in humidity, which can cause buckling’.…”
Section: Writing As Palimpsestmentioning
confidence: 99%
“…In cases where revisions are required, the feedback from reviewers and editorial guidance should in principle support the authors in developing a stronger paper. Brewis (2018) goes even further to suggest that reviewers and editors are de facto co-authors of the papers they evaluate 4 . There is some truth in this view as oftentimes manuscripts end up making a clearer and stronger contribution with the support of constructive comments from peer-reviewers.…”
Section: Convention and Conversationsmentioning
confidence: 99%
“…Some argued that this power, rooted in the system of academic journal ranking (Willmott 2011), is the power not only to accept or reject a manuscript but also to infringe at will upon the intellectual integrity of the authors' submissions (Frey 2003). Brewis (2018) observed that the referees' comments and suggestions can be exceedingly lengthy and changing the manuscripts as per their recommendations can amount to writing a separate paper. In the same vein, others lamented that editorial teams tend not to provide an assessment of the worth of the manuscript but rather force the authors into re-writing the submission according to the referees' personal preferences (Driver 2007), expectations of formulaic conformity (Alvesson and Gabriel 2013), and prescribed presentation of evidence and arguments (Honig et al 2018).…”
Section: The Americanisation Of Management Research Publishingmentioning
confidence: 99%